EVANS SYNDROME : A CASE REPORT - N. Khaira, Fauzio; Syaikhul I, Mohamad; Rahman, Arief A.; Rijal, Selfie C. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Evans Syndrome (ES) is a rare autoimmune disorder characterized by the presence of autoimmune hemolytic anemia (AIHA) and immune thrombocytopenia purpura (ITP). The average patients were diagnosed at the age of 52 years with a female-to-male ratio of 3:2. A 43-year-old woman, with complaint of spontaneous bleeding of the gum ten hour prior to hospital. Pressure bandages have been applied but bleeding still occurs. There was no previous history of bleeding disorder or family history of bleeding disorder. There are ulcers that occur spontaneously on the left thigh and lower leg. The patient has a history of 5 miscarriages. The patient comes with stable vital signs. Physical examination shows anemic conjunctiva, active bleeding in the left gum, ulcers on the back of the left thigh and on the left lower leg. Laboratory findings showed hemoglobin 6.0, leukocytes 4770, platelets 79.000, reticulocytes 1.8%. BUN and electrolyte were normal. Peripheral blood morphology shows normochromic normocytic anemia with increased erythropoietic response and thrombocytopenia suggests a chronic process with bleeding. Immunoserological examination shows direct antiglobulin test (DAT) +1, immature platelet fraction (IPF) 7.9%. HIV test, anti-HCV and HBsag were non-reactive. The therapy given includes high-dose steroids, antibiotic, blood transfusions and symptomatic therapy. The patient was discharged after 6 days with clinical recovery. Laboratory findings of normochromic normocytic anemia with DAT +1 results suggest AIHA. Thrombocytopenia in a patient with elevated IPF suggest ITP. The presence of these two findings leads to the diagnosis of ES. A spontaneous ulcer can be a sign of blood vessel thrombosis that can occur in ES. History of recurrent miscarriage leads to secondary ES with antiphospholipid syndrome (APS). Futher blood test is needed to determine the cause of bleeding and antiphospholipid syndrome.